Calcium Phosphate Cement Composed of Hydroxyapatite Modified Silica and Polyeugenol as a Bone Filler Material - Tri Windarti; Nor Basid Adiwibawa Prasetya; Ngadiwiyana Ngadiwiyana; Limpat Nulandaya (Universitas Gadjah Mada, 2023)
A composite of hydroxyapatite modified silica (HASiO2) and 10% (w/w) polyeugenol (PE) was synthesized to produce a calcium phosphate cement with antibacterial activity. The compatibility of the composite (HASiO2_PE) with bone filler requirements was determined due to its crystal, surface, antibacterial, and cytocompatibility properties. The results showed that compositing HASiO2 and PE did not affect HA's chemical dan crystal properties. The presence of PE changed HASiO2 morphology to be coarser and denser than before composited. PE tends to agglomerate but does not affect the hydrophilicity of HASiO2. The presence of PE increased the surface area and total pore volume but lowered the average pore size. Different from pure PE, the composite of HASiO2_PE that contains of 10% PE has higher antibacterial activity toward Escherichia coli than Staphylococcus aureus. The composite is biocompatible because the cytotoxicity test toward pre-osteoblast cells resulted in an IC50 of 2092 μg/mL. Thus, due to its chemical, surface, antibacterial, and cytocompatibility properties, the HASiO2_PE composite can be recommended as a bone filler material.